Mechanical Processing with Solid-State of Supercapacitor Materials: A Review of High Energy Milling and High Velocity Particle Methods - Mahruri Arif Wicaksono; Bambang Suharno; Widi Astuti; Yayat Iman Supriyatna; Slamet Sumardi (Jurnal Polimesin, 2024)
Supercapacitors have emerged as a crucial energy storage technology, bridging the gap between traditional capacitors and batteries. The performance of supercapacitors is heavily dependent on the properties of the electrode materials used. Mechanical processing methods, particularly High Energy Milling (HEM) and High-Velocity Particle (HVP) methods have shown great promise in enhancing the physical and electrochemical properties of supercapacitor materials. This review explores the fundamental principles, mechanisms, and recent advancements in HEM and HVP techniques for the synthesis and modification of supercapacitor materials. High energy milling, including ballmill and attritor milling, facilitates particle size reduction, increased surface area, and the creation of nanostructures, leading to improved capacitance and energy density. High velocity particle methods, such as cold spraying and thermal spraying, enable the deposition of uniform and dense coatings, enhancing conductivity and stability. The review also discusses the impact of process parameters on material properties, the challenges faced in scaling up these techniques, and the potential future directions for research. By providing a comprehensive overview of these mechanical processing methods, this paper aims to highlight their significance and potential in advancing supercapacitor technology.